STRATEGI BERSAING DALAM MENINGKATKAN KINERJA PERUSAHAAN PADA BISNIS JASA PERHOTELAN - Eka Setiajatnika; Muhamad Ardi Nupi Hasyim (Coopetition : Jurnal Ilmiah Manajemen, 2019)
Research on Corporate Competitive Strategies in Increasing Number of Guest Visits In The Hospitality Business (Case Study At Four Star XYZ Hotel in Tangerang City,) highlights how the company achieves competitiveness and improves its performance. In running its business Hotel XYZ faced problems, namely decreasing the number of guest visits and weak competitiveness of the company. This research used qualitative method by using descriptive approach. For data collection method used is by giving questionnaires to hotel customers and interviews to informants who then analyze the data based on the IFE and EFE matrix. Based on the research results found that the current level of company indicates that XYZ Hotel is still in the average level, so XYZ hotel should make a good strategy for the future the company can achieve the vision and mission of the company. Based on the analysis of IFE and EFE Hotel XYZ is in quadrant five so that strategy can be done by Hotel XYZ to improve the competitiveness of company by doing competition through differentiation.